Quais técnicas de assistência respiratória são eficazes para melhorar a função pulmonar em indivíduos com doença neuromuscular? Uma revisão sistemática com meta-análise - Costa, Ester Laura Cordeiro Oliveira (Universidade Federal de São Carlos, 2025)
Conduct a literature review in databases through randomized clinical trials, aiming to establish which respiratory assistance techniques are effective in improving pulmonary function in individuals with neuromuscular diseases. Data Sources The search was conducted in the Cinahl, Cochrane Library, Embase, PubMed, PEDro, Ovid, and Web of Science databases, aiming to maximize data collection for integration into the systematic review. Article Selection Only randomized controlled trials investigating the efficacy of respiratory assistance techniques were included, excluding the application of invasive mechanical ventilation for respiratory failure, in assessing pulmonary function in individuals of both sexes with a clinical diagnosis of neuromuscular diseases. Data Extraction The reviewers independently extracted the data, and subsequently, another reviewer verified the collected data to prevent any typing or other errors. The data were exported to an Excel spreadsheet. Data Synthesis The authors created tables to present the selected studies, allowing clinicians to find these studies in a summarized form when reading this review. Additionally, a meta-analysis was performed using the values reported in the studies. Results A total of 1267 studies were identified, but only 7 were included in the meta-analysis (n = 342, with a mean age of 42.92 for the control group and 39.33 for the intervention group). The interventions improved forced vital capacity (MD = 0.10, 95% CI 0.12 to 0.18 L) and predicted forced vital capacity (MD = 1.99, 95% CI 0.98 to 3.00%). Conclusion The results provided a greater understanding of the effects of respiratory assistance techniques and allowed the conclusion that NIV and MI-E proved to be more effective for pulmonary function.
Which respiratory assistance techniques are effective in improving lung function in individuals with neuromuscular disease? A systematic review with meta-analysis
Keywords: Doença neuromuscular; Empilhamento de ar; Fisioterapia torácica; Função pulmonar; Fisioterapia; Lung function; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL